(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
This essay is part of a broader investigation about the discussion around the concepts of civilization and barbarism in Latin America. We trace back to the role in the configuration of this discursive played by Hernán Cortés, who was projected as a «civilizing hero» for contributing to the spread of Christianity in the New World, as well as for his role as ruler, settler, urban planner and architect of the new colonial order. As a balance, a proposal is offered, inspired by Walter Benjamín, around the conception of Cortés as a «civilizer» that aims to challenge the Manichaeism from which he is usually conceptualized.